2005
DOI: 10.1523/jneurosci.1085-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reversible Changes in Dendritic Spine StructureIn VivoGated by the Degree of Ischemia

Abstract: Current therapeutic windows for effective application of thrombolytic agents are within 3-6 h of stroke. Although treatment can improve outcome, it is unclear what happens to synaptic fine structure during this critical period in vivo. The relationship between microcirculation and dendritic spine structure was determined in mouse somatosensory neurons during stroke. Spines were, on average, 13 m from a capillary and were supplied by ϳ100 red blood cells per second. Moderate ischemia (ϳ50% supply) did not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
258
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(271 citation statements)
references
References 24 publications
9
258
1
3
Order By: Relevance
“…Minimum intensity Z-projections from selected dendrites were created in ImageJ (NIH) as described from z-series collected at 100ϫ magnification (Schneider et al, 2012). Observations were performed by a blind observer in the distal dendrites of neurons originated from cortical layer V within 0.6 mm from the border of the necrotic core, between 0 and ϩ 0.5 mm anterior to bregma where the digits of the right forelimb are represented (Tennant et al, 2011) and plastic changes ensue following an ischemic lesion (Zhang et al, 2005;Brown et al, 2007;Li and Murphy, 2008). The number and length of protrusions, as well as the percentage of neurons with dendritic varicosities, were quantified in the distal dendrites of 10 neurons per section, in five cuts per animal, in 12 animals per experimental group (n ϭ 600 dendrites) with Image MetaMorph Software in pictures magnified 200% of their original size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum intensity Z-projections from selected dendrites were created in ImageJ (NIH) as described from z-series collected at 100ϫ magnification (Schneider et al, 2012). Observations were performed by a blind observer in the distal dendrites of neurons originated from cortical layer V within 0.6 mm from the border of the necrotic core, between 0 and ϩ 0.5 mm anterior to bregma where the digits of the right forelimb are represented (Tennant et al, 2011) and plastic changes ensue following an ischemic lesion (Zhang et al, 2005;Brown et al, 2007;Li and Murphy, 2008). The number and length of protrusions, as well as the percentage of neurons with dendritic varicosities, were quantified in the distal dendrites of 10 neurons per section, in five cuts per animal, in 12 animals per experimental group (n ϭ 600 dendrites) with Image MetaMorph Software in pictures magnified 200% of their original size.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral ischemia has a direct impact on the integrity of these structures. Indeed, two landmark in vivo studies using two-photon microscopy showed that whereas dendritic spines inside the necrotic core are irreversibly damaged, those located within 0.6 mm from its border are replaced by areas of focal swelling, known as dendritic varicosities; remarkably, if reperfusion occurs within 60 min of the onset of the ischemic injury, a variable proportion of spines in this area re-emerge again from these varicosities (Zhang et al, 2005;Li and Murphy, 2008). This highly plastic nature of dendritic spines bestows on them a fundamental role in the recovery process from an ischemic stroke (Brown et al, 2007;Murphy and Corbett, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…72,73 It is understood that although in what follows the term SNL will be used generically when referring to reduced in vivo cBZR mapping, this marker may in fact reveal neuronal damage in addition to actual death.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Des modifications structurales des neurones du réseau synaptique et des épines dendritiques [23,24], consé-cutives à l'activation des NMDAR, sont constatées. Certains de ces changements morphologiques sont toutefois réversi-bles [25]. Chez le rat, un arrêt cardiaque de huit minutes diminue le nombre d'épi-nes dendritiques dans CA1 et perturbe sélectivement la mémoire spatiale [26].…”
Section: Plasticité à Long Terme Des Récepteurs Nmdaunclassified